Political Communication Strategy of Young Parliamentary Candidates and the Millennial Generation to Reach Young Voters (Qualitative Study on DPRD Candidates in Hulu Sungai Utara Regency) - Hindayani, Lia; Hayat, Muzahid Akbar; Lihu, Decky C Kananto; Novianti, Lieta Dwi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the political communication strategies implemented by young parliamentary candidates, especially the millennial generation, in reaching young voters in the 2024 Election in Hulu Sungai Utara Regency. The method used is descriptive qualitative with direct observation approaches, in-depth interviews, document studies, and participatory observations. The results of the study show that millennial parliamentary candidates utilize mass and digital media, such as social media and mobile devices, as the main means to reach young voters. The uses and gratifications theory emphasizes that millennials actively choose media that suits their needs, making digital media the main instrument in political communication. However, major challenges arise from low historical literacy and the prevalence of fake news (hoaxes), which can damage the credibility of candidates and parties. To overcome these obstacles, a community-based strategy is needed, both physically and online, to build trust through offline discussions and positive literacy. With this approach, millennial candidates are expected to be able to convince young voters of their ability to bring change and progress in regional development.